PRACTICALITY AND EFFECTIVENESS OF PTERYDOPHYTA DIVERSITY E-ENCYCLOPEDIA IN IMPROVING CRITICAL THINKING SKILLS - Yudhistian, Yudhistian; Wulandari, Tabitha Sri Hartati (IJIET (International Journal of Indonesian Education and Teaching), 2025)
This represents an advanced Research and Development (R&D) study designed to evaluate the practicality and effectiveness of an e-encyclopedia which has been built and validated with very valid results. The fourteen students who formed up the research subjects. Pre-test and post-test questionnaires, observation sheets, and student response questionnaires were used as the study instruments. The study data analysis technique was descriptive quantitative through three stages, namely calculating the percentage value of practicality and effectiveness tests, Mann-Whitney U non-parametric test, and N-Gain (g) test. An average percentage value of 85.63% was attained with a very practical category in the practicality test analysis findings. With a percentage score of 81.13%, the effectiveness test analysis revealed a very strong response from the students. In contrast, there was a significant difference between the pre-test and post-test findings in terms of raising CTS by 0.78 with a high category, according to the effectiveness test analysis results using the Mann-Whitney U test and the N-Gain (g) test. The conclusion shows that Canvaflipedia to improve CTS is proven to be practical and effective, so it is suitable for use.